Estratégias de ensino aprendizagem no ensino técnico de enfermagem - Nascimento, Michelle Santana do [UNIFESP] (2018)
In Brazil, The Number Of Technical Training Schools In Nursing Has Increased In Recent Times, Mainly Due To The Demand For Employment In This Area. The Technical Courses Require Nursing Teachers, Who Have The Baccalaureate Training, With Competencies For Health Care And Not Specifically To Work As A Teacher. In This Context, Technical Schools Have The Responsibility Of Training Professionals Capable Of Providing Quality Health Care. The Nurse Needs To Be More And More Prepared To Work As A Teacher So That He Understands The Importance Of The Student Teacher Relationship, The Teaching-Learning Process, The Needs To Use Educational Practices That Enable Reflection, Criticism And The Construction Of Knowledge Based On Problems That Occur Daily In The Classroom, As Well As Work In Supervised Internship Camps. Through The Presented Appeared The Need For Reflection And Analysis On The Teaching-Learning Strategies Of Nurse-Teachers, Who Work In The Training Of Nursing Technicians. The Present Research Aims To Unders